The Correlation Of Women of Childbearing Age’ Education And Work With Use Of Internal Contraceptive Devices (IUD) - Damayanti, Tri Yunita Fitria; Zulaikha , Layla Imroatu; Wulandari, Tiwuk (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
Current family planning programs are urgently needed to prevent unwanted pregnancies and to improve the health and well-being of mothers and children. One of them is the IUD is a long-term contraceptive method that has a high level of effectiveness. The IUD is the third most commonly used method in Asia. This study aims to determine whether there is a relationship between education and work of women of childbearing age with the use of IUDs at the Temandang Health Center, Merakurak Subdistrict, Tuban . This research was conducted in July 2022 at the Temandang Health Center. This research methodology uses observational analytic with cross sectional design. The independent variables are education and work, while the dependent variable is IUD use. The population in this study were all active family planning acceptors at the Temandang Merakurak Health Center, a sample of 177 family planning acceptors was obtained using simple random sampling technique. Data processing used the chi square test with a significance level of <0.05. The results of the study of 177 female respondents of childbearing age, half of them had low education, almost all of them did not work and were not IUD acceptors. After statistical test using SPSS ρ -value 0.000, then H₀ is rejected. This proves that there is a relationship between education and occupation of women's reproductive organs with the use of IUDs at the Temandang Health Center, Merakurak Subdistrict, Tuban . The results of this study can provide input and information from several supporting factors that influence a woman of childbearing age following the family planning program so that health workers can optimize health promotion for couples of childbearing age in choosing the most appropriate contraceptive according to their needs and conditions.